2018
DOI: 10.1002/mdc3.12714
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Levodopa on Speech Dysfluency in Parkinson's Disease

Abstract: Objective Objective: To examine the effect of levodopa medication on speech dysfluency in Parkinson's disease. MethodsMethods: Fifty-one individuals with Parkinson's disease (IWPD) read aloud during offand onmedication states. Total speech dysfluencies were calculated from transcriptions of recorded speech samples. ResultsResults: Severity of speech dysfluency was not significantly related to the severity of motor symptoms, duration of disease, levodopa equivalent dosage, or age. When the IWPD were divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
2
15
2
Order By: Relevance
“…Finally, when investigating the effects of Levodopa on developmental stuttering, Anderson et al [14] reported an increase of disfluencies in the spontaneous speech of 1 patient during the ON period. This is in disagreement with the findings of Im et al [15], which examined 51 patients while reading a standard passage. In fact, the authors found an improvement of disfluency in the ON state that was proportional to the severity of speech impairments presented in the OFF state.…”
Section: Related Workcontrasting
confidence: 91%
See 1 more Smart Citation
“…Finally, when investigating the effects of Levodopa on developmental stuttering, Anderson et al [14] reported an increase of disfluencies in the spontaneous speech of 1 patient during the ON period. This is in disagreement with the findings of Im et al [15], which examined 51 patients while reading a standard passage. In fact, the authors found an improvement of disfluency in the ON state that was proportional to the severity of speech impairments presented in the OFF state.…”
Section: Related Workcontrasting
confidence: 91%
“…However, while the effects of dysarthria in PD have been deeply investigated, both in drug-naive state and under pharmacological treatment [4][5][6][7][8][9], it is still not clear whether speech analysis could be helpful to differentiate between ON-OFF states induced by pharmacological intake. In fact, the clinical literature presents controversial results on the effect of Levodopa on speech abilities [10][11][12][13][14][15], while no computational studies addressing this topic have been identified in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Ikeda et al showed that the increase in L-dopa daily dose was greater in patients without a decline in cognitive function. [58] However, higher total LEDD Clinical meaning of LEDD has been reported on the one hand in patients with speech dysfluencies compared with fluent patients [59] and on the other hand, as a risk factor of executive function decline post-STN-DBS. [60] Concerning psychosis, Lenka et al illustrated that higher total LEDD may not trigger early occurrence of psychosis in PD patients.…”
Section: Ledd and Non-motor Symptomsmentioning
confidence: 99%
“…Although Im et al (2019) conclude that the comparison of the PD participants in the ON state vs. OFF state conditions did not reach statistical significance, the last explorations performed recently, based on machine and deep learning by Norel et al (2020); Pompili et al (2020) reported higher accuracies of ON and OFF classification. Norel et al (2020) analyzed voice of PwPD describing a picture, speaking reverse counting, and diadochokinetic rate speech tasks.…”
Section: Related Workmentioning
confidence: 76%
“…Tykalová et al (2015) found a strong positive correlation between the total cumulative dose of levodopa and the increased occurrence of dysfluent words and stuttering. Likewise, results from Im et al (2019) indicate that levodopa medication can significantly affect speech dysfluency, primarily associated with the severity of the OFF medication. Speech analysis has been done on a standard Rainbow passage reading task.…”
Section: Related Workmentioning
confidence: 99%